PEMANFAATAN HUTAN PRODUKSI DI DESA MALINO KECAMATAN SOYOJAYA KABUPATEN MOROWALI UTARA - Golar, Golar; Alam, Andi Sahri; Nurnaningsih, Nurnaningsih (ForestSains, 2017)
Forest production area is a forest area which its main function is for production purpose in order to obtain the maximum economic benefits considering the natural preservation of environmental functions and the existence of the forest production area itself. This study aimed to determine the forms of utilization of forest productions which were done by the people in Malino Village, Soyo Jaya District, North Morowali Regency. The total population in the study area consisted of 130 households so that the number of samples in this study was 25% (32 people) of the total population. The purposive sampling was chosen purposively. This study was conducted in 3 months, starting from January to March 2016 in Malino Village, Soyo Jaya District, North Morowali Regency. The data analysis used in this research was descriptive analysis. The results showed that the people of Malino Village used the land for gardening and farming. Plants consisted of corn, candlenut, chocolate, red beans, cloves, avocadoes, durians, and vegetables. The most used forest product was candlenut (68.75%), where the utilization of candlenuts was done 4 times a year. In addition, the community also used rattan (12.50%), in which the data showed that each person used Â± 30-40 kg of raw rattan, and harvesting was done 6 times a year. Meanwhile, people who utilized resin indicated low category of (6.25%), and the result was that each person utilized Â± 15-20 kg. This indicated that most people utilized non-timber forest products